Cry of silenced peoples: Linguistic and cultural intermediaries between two worlds: History and mentalities - Glave, Luis Miguel (1990)
According to an old conception of history as a science, as structured and controlled historical knowledge, it does not properly appear except with writing. If we agreed with them, the Andean men and women would not have had a history until when others wrote it for them. The date: 1532. The authors: the European men who conquered and colonized the Andean peoples.